DIAGNOSIS AND TREATMENT OF CHRONIC BRUCELLOSIS (Modern education and development, 2025)
We followed up 85 patients aged from 17 to 74 years. Standard general, serological, biochemical and statistical methods were used in all patients. Patients according to clinical forms were distributed as follows: primary chronic brucellosis (BCB) - 22 (25,8%) and secondary chronic brucellosis (SCB) - 63 (74,2%). Subcompensation phase was observed in 62,3% of examined patients, decompensation phase was revealed in 37,7%.